The prescription of antiplatelet medication in a very elderly population: An observational study in 15 141 ambulatory subjects. Issue 12 (21st September 2017) - Manckoundia, Patrick; Buzens, Jean‐Baptiste; Mahmoudi, Rachid; d'Athis, Philippe; Martin, Isabelle; Laborde, Caroline; Menu, Didier; Putot, Alain
Summary: Objective: Despite the frequent use of antiplatelet medication (AM) in the elderly patients, very few studies have investigated its prescription. We describe AM prescription through retrospective study in ambulatory elderly patients. Method: All subjects aged over 80 years with a medical prescription delivered in March 2015 and affiliated to the Mutualité Sociale Agricole de Bourgogne . Subjects with prescriptions for AM were compared with those without. Results: A total of 15 141 ambulatory elderly patients (83‐89 years, 61.3% of women) were included and 4412 (29.14%) had a prescription for AM. The latter were more frequently men than those without AM (43% vs 36.93%, P < .0001) and more frequently had chronic comorbidities (77.24% vs 64.65%, P < .0001). Compared with ambulatory subjects without AM, those with AM more frequently had coronary heart disease (35.15% vs 14.49%), severe hypertension (30% vs 25.65%), diabetes (27.42% vs 20.64%), peripheral arterial diseases (16.28% vs 5.96%) and disabling stroke (9% vs 5.56% (all P < .0001). In addition, they had more prescriptions of beta‐blockers (45.24% vs 36.90%), angiotensin conversion enzyme inhibitor (31.35% vs 25.44%), calcium channel blockers (33.34% vs 27.90%), nitrate derivatives (10.6% vs 6.03%) or hypolipidemic agents (HA; 49.81% vs 29.72%) (all P < .0001) than those without AM. Conclusion: In this study, which is very interested for its size and the advanced age of the subjects, long‐course AM was prescribed in one third of ambulatory elderly patients. Coronary heart disease, severe hypertension and diabetes were more frequent in AM subjects. However, the low percentage of declared strokes was surprising. We provide additional data to doctors following subjects with AM.